Hematopoietic stem cell transplantation for adults with Philadelphia chromosome-negative acute lymphoblastic leukemia in first remission: a position statement of the European Working Group for Adult Acute Lymphoblastic Leukemia (EWALL) and the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation (EBMT) - Giebel, Sebastian; Marks, David I; Boissel, Nicolas; Baron, Frederic; Chiaretti, Sabina; Ciceri, Fabio; Cornelissen, Jan J; Doubek, Michael; Esteve, Jordi; Fielding, Adele; Foa, Robin; Gorin, Norbert-Claude; et al. (Bone marrow transplantation, 2019)
Allogeneic hematopoietic stem cell transplantation (HSCT) in first complete remission is a standard of care for adult patients with Philadelphia chromosome (Ph)-negative acute lymphoblastic leukemia (ALL) and high risk of relapse. However, the stratification systems vary among study groups. Inadequate response at the level of minimal residual disease is the most commonly accepted factor indicating the need for alloHSCT. In this consensus paper on behalf of the European Working Group for Adult Acute Lymphoblastic Leukemia and the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation, we summarize available evidence and reflect current clinical practice in major European study groups regarding both indications for HSCT and particular aspects of the procedure including the choice of donor, source of stem cells and conditioning. Finally, we propose recommendations for daily clinical practice as well as for planning of prospective trials.
Keywords: Hematopoietic Stem Cell Transplantation; Female; indukce remise; transplantace hematopoetických kmenových buněk; akutní lymfatická leukemie; příprava pacienta k transplantaci; Transplantation Conditioning; Humans; ženské pohlaví; mužské pohlaví; prospektivní studie; lidé; Male; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Europe; Evropa; Remission Induction; Prospective Studies